2017
DOI: 10.1007/s12010-017-2421-8
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Oil Production by the Tropical Marine Diatom Thalassiosira Sp. Cultivated in Outdoor Photobioreactors

Abstract: Microalgae-derived oils have potential as a biofuel feedstock. To produce microalgal oils at a large scale, large amounts of nutrients and energy are needed to grow the algae. In this study, we evaluated three types of agricultural fertilizer (AF)-based culture media (AF1, AF2, and AF3) based on a previously published enriched seawater (ES) medium to produce biomass and oils from Thalassiosira sp. Under laboratory conditions, the highest cell productivity of Thalassiosira sp. was obtained with the AF3 medium. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…The dry weight biomass of outdoor culture of N. palea (x′ = 0.16, n = 24) was significantly (P ≤ 0.05) lower than that under laboratory conditions (x′ = 0.27, n = 8). Moreover, the percentage dry weight biomass (% dw) of the n-hexane eluate of intracellular lipids of this diatom was higher under laboratory (26.2% dw) than under outdoor growth (8.54% dw) conditions, These results are in a perfect agreement with previous findings ( Hu et al, 2008 , Hu et al, 2006 , Starr, 1978 , Sharma and Singh, 2009 , Pintaka et al, 2017 , Almutairi, 2020 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The dry weight biomass of outdoor culture of N. palea (x′ = 0.16, n = 24) was significantly (P ≤ 0.05) lower than that under laboratory conditions (x′ = 0.27, n = 8). Moreover, the percentage dry weight biomass (% dw) of the n-hexane eluate of intracellular lipids of this diatom was higher under laboratory (26.2% dw) than under outdoor growth (8.54% dw) conditions, These results are in a perfect agreement with previous findings ( Hu et al, 2008 , Hu et al, 2006 , Starr, 1978 , Sharma and Singh, 2009 , Pintaka et al, 2017 , Almutairi, 2020 ).…”
Section: Discussionsupporting
confidence: 92%
“…The outdoor production of lipids and biomass were monitored for a full annual cycle, involving distinct seasonal variations in ambient temperature and radiant energy, parameters shown to control algal biomass development ( Reynolds, 1984 ) and lipid production ( Haas et al, 2009 , Hu et al, 2008 , Sharma and Singh, 2009 , Matsumoto et al, 2017 , Pintaka et al, 2017 ). The dry weight biomass of N. palea varied considerably between 0.11 g l −1 and 0.25 g l −1 with a mean annual value of 0.16 g l −1 .…”
Section: Discussionmentioning
confidence: 99%
“…was 50% higher during the rainy season than in the dry season. However, the biomass had a higher content of saturated fatty acids during the dry season and more unsaturated fatty acids during the rainy season [121]. In the dry season, the culture received twice the solar irradiance compared with the rainy season.…”
Section: Effect Of Varying Outdoor Conditionsmentioning
confidence: 97%
“…A study conducted in Indonesia showed that Thalassiosira sp. grown during rainy and dry seasons had different biochemical compositions [121]. Carlozzi and Sacchi (2001) observed a mean Lowry protein content of Rhodopseudomonas palustris that decreased by around 2% in July compared with January, and crude protein always remained 10% higher than Lowry protein content [104].…”
Section: Downstream Processesmentioning
confidence: 99%
See 1 more Smart Citation